Get reliable answers to your questions at Westonci.ca, where our knowledgeable community is always ready to help. Explore a wealth of knowledge from professionals across various disciplines on our comprehensive Q&A platform. Experience the convenience of finding accurate answers to your questions from knowledgeable experts on our platform.

Determine the roots of [tex]$2x(x-3)=3x+5$[/tex] by completing the square.

Sagot :

Sure, let's determine the roots of the given equation [tex]\(2x(x-3)=3x+5\)[/tex] by completing the square. Here is the step-by-step solution:

1. Rewrite the equation in standard quadratic form:

Start with the given equation:
[tex]\[ 2x(x-3) = 3x + 5 \][/tex]

Expand and simplify the left-hand side:
[tex]\[ 2x^2 - 6x = 3x + 5 \][/tex]

Move all terms to one side to set the equation to zero:
[tex]\[ 2x^2 - 6x - 3x - 5 = 0 \][/tex]

Combine like terms:
[tex]\[ 2x^2 - 9x - 5 = 0 \][/tex]

2. Identify the coefficients:

For the equation [tex]\(2x^2 - 9x - 5 = 0\)[/tex], the coefficients are:
- [tex]\(a = 2\)[/tex]
- [tex]\(b = -9\)[/tex]
- [tex]\(c = -5\)[/tex]

3. Complete the square:

To complete the square, we need to transform the quadratic equation into a perfect square form. Here’s the detailed process:

a. Move the constant term to the other side:
[tex]\[ 2x^2 - 9x = 5 \][/tex]

b. Divide the entire equation by the leading coefficient [tex]\(a = 2\)[/tex]:
[tex]\[ x^2 - \frac{9}{2}x = \frac{5}{2} \][/tex]

c. To complete the square, take half of the coefficient of [tex]\(x\)[/tex], square it, and add it to both sides:

The coefficient of [tex]\(x\)[/tex] is [tex]\(-\frac{9}{2}\)[/tex]. Half of this is [tex]\(-\frac{9}{4}\)[/tex]. Squaring it, we get:
[tex]\[ \left(-\frac{9}{4}\right)^2 = \frac{81}{16} \][/tex]

Add [tex]\(\frac{81}{16}\)[/tex] to both sides:
[tex]\[ x^2 - \frac{9}{2}x + \frac{81}{16} = \frac{5}{2} + \frac{81}{16} \][/tex]

d. Simplify the right side:
Convert [tex]\(\frac{5}{2}\)[/tex] to a fraction with a denominator of 16:
[tex]\[ \frac{5}{2} = \frac{40}{16} \][/tex]

Adding the fractions:
[tex]\[ \frac{40}{16} + \frac{81}{16} = \frac{121}{16} \][/tex]

Now we have:
[tex]\[ x^2 - \frac{9}{2}x + \frac{81}{16} = \frac{121}{16} \][/tex]

e. Left side is a perfect square:
[tex]\[ \left( x - \frac{9}{4} \right)^2 = \frac{121}{16} \][/tex]

4. Solve for [tex]\(x\)[/tex]:

Take the square root of both sides:
[tex]\[ x - \frac{9}{4} = \pm \frac{\sqrt{121}}{4} \][/tex]
[tex]\[ x - \frac{9}{4} = \pm \frac{11}{4} \][/tex]

5. Consider both cases for solutions:

a. [tex]\( x - \frac{9}{4} = \frac{11}{4} \)[/tex]:
[tex]\[ x = \frac{9}{4} + \frac{11}{4} = \frac{20}{4} = 5 \][/tex]

b. [tex]\( x - \frac{9}{4} = -\frac{11}{4} \)[/tex]:
[tex]\[ x = \frac{9}{4} - \frac{11}{4} = \frac{-2}{4} = -\frac{1}{2} \][/tex]

So, the roots of the given equation [tex]\(2x(x-3) = 3x + 5\)[/tex] are:
[tex]\[ x = 5 \quad \text{or} \quad x = -\frac{1}{2} \][/tex]
Thanks for stopping by. We strive to provide the best answers for all your questions. See you again soon. We appreciate your time. Please revisit us for more reliable answers to any questions you may have. Thank you for using Westonci.ca. Come back for more in-depth answers to all your queries.